2002
DOI: 10.1038/4151022a
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive protein evolution in Drosophila

Abstract: For over 30 years a central question in molecular evolution has been whether natural selection plays a substantial role in evolution at the DNA sequence level. Evidence has accumulated over the last decade that adaptive evolution does occur at the protein level, but it has remained unclear how prevalent adaptive evolution is. Here we present a simple method by which the number of adaptive substitutions can be estimated and apply it to data from Drosophila simulans and D. yakuba. We estimate that 45% of all ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
712
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 650 publications
(747 citation statements)
references
References 17 publications
31
712
4
Order By: Relevance
“…To identify the proportion of differences fixed by positive selection, we calculated the average proportion of amino-acid substitutions driven by positive selection (alpha), using equation (3) in Smith and Eyre-Walker 22 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the proportion of differences fixed by positive selection, we calculated the average proportion of amino-acid substitutions driven by positive selection (alpha), using equation (3) in Smith and Eyre-Walker 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Confidence intervals of alpha were obtained through bootstraps (1,000 bootstraps) by randomly selecting genes with replacement as described in Smith and EyreWalker 22 . In this case, substitutions (D) were considered as SNPs in the top three percentile of the F ST distribution and polymorphisms, the bottom 97 percentile.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has suggested that a substantial fraction of nonsynonymous substitutions in Drosophila were fixed through positive selection [81][82][83][84][85] . We estimate that 33.1% of single-copy orthologues in the melanogaster group have experienced positive selection on at least a subset of codons (q-value true-positive tests 77 ) (Supplementary Information section 11.1).…”
Section: Articlesmentioning
confidence: 99%
“…Several studies using the MK test show a high level of 'positive selection' on between-species aminoacid differences in comparisons between D. melanogaster and other Drosophila species (Smith and Eyre-Walker, 2002;Sawyer et al, 2007;Shapiro et al, 2007), whereas in human-chimpanzee comparisons, a much lower proportion of genes show evidence of 'positive selection' (Bustamante et al, 2005;Gojobori et al, 2007).…”
Section: The Mcdonald-kreitman Testmentioning
confidence: 99%